Analisis Lokasi Perusahaan Dan Pelayanan terhadap Kepuasan Pelanggan Studi Kasus pada PT. Hotel Salak The Heritage Bogor - Sume, Syahlan A (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
The purpose of this research is to analyze the influence of firm and service in creating satisfaction for consumers. This analysis was done by conducting questionaire to one hundred respondents, id est users of hotel service. The result of this research shows that evaluation to the firm as consumers perceive nowadays is good. By utilizing analysis of performance-importance mean, it can be found out that performance mean to consumersâ satisfaction is between 3,77 â 4,79, whereas importance mean to consumersâ satisfaction is between 4,23 â 4,66. Based on scale range of mean analysis, it shows good appraisal. Two variables (location and service) extend influence as high as 90,2% to consumersâ satisfaction, so it is good. It can be concluded that location and service have influence towards customersâ satisfaction. Keywords: Consumersâ satisfaction; Service.